The effectiveness of the use of self-learning materials and the lecture method in high school physics - Portugal, Hideliza Leyson 1950- (1977)
The experimental study was undertaken to find out the effects of the use of self learning materials on the achievement of high school students in physics, as compared to the lecture method. The Wilcoxon Matched-Pairs Signed-Ranks test was used in the analysis of the pre-test and post-test results. Results showed that there is a significant difference between the achievement of students subjected to the use of self learning materials and that of students subjected to the lecture method of instruction. The difference favored the innovative teaching method under study.
Appendices: leaves 28-90
Mimeographed.
Thesis (M.A.T.)--University of the Philippines, Quezon City
Vita
Keywords: Physics -- Self-instruction.; Physics -- Study and teaching